THE RELATIONSHIP OF PARENTS' ATTENTION AND LEARNING INDEPENDENCE ON MATHEMATICS LEARNING ACHIEVEMENT IN GRADE VII STUDENTS - Ety Wahyuni; Widayati Widayati (Universitas Ahmad Dahlan, 2019)
Low student achievement is closely related to many factors, one of which is parents' attention and learning independence on the learning achievement. This study aimed to determine whether there is a positive and significant relationship between parents' attention and learning independence on mathematics learning achievement in grade VII students at State Islamic Junior High School (MTs Negeri) 6 Kulon Progo in the academic year 2019/2020. The population in this study were students of grade VII at MTs Negeri 6 Kulon Progo in the academic year 2019/2020, consisting of classes VII A, VII B, VII C, and VII D with a total of 128 students. The sample was taken from class VII A as a research sample and carried out by a purposive sampling technique. The researcher used a questionnaire method to collect data on parents' attention and learning independence. At the same time, the test method was used to determine mathematics learning achievement. Research instruments include validity tests, different power tests, and reliability tests. Requirements analysis includes a normality test, linearity test, and independence test. The researcher used product-moment correlation analysis and multiple linear regression analysis to analyze data. The results showed a positive and significant relationship of parents' attention and learning independence on the mathematics learning achievement in Grade VII students at MTs Negeri 6 Kulon Progo in the academic year 2019/2020. This was indicated by Â which was 8.48355> 3.32765 with R = 0.60754 and =0.36911 with RC Â = 31.85638%, RC = 68.14361% and EC = 11.75863 %, EC Â = 25.15276%.